The effect of changing-speed on the toe height on treadmill running - Chang, Y. H.; Chi, P. W.; Chiu, H. T. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this investigation is to observe the differences of foot trajectory when having changing-speed running in treadmill. Subjects running on a treadmill at three different speeds and performing a dynamic data from the mark in toe box and heel counter. The result shows that with increased speed the first peak toe height just after toe-off and toe clearance (TC) increased significantly, and decreased significantly with decreased speed. The result has significant different from walking. In addition, one of four subjects has more obvious foot flat than other subjects. The reason of this phenomenon is still unclear, and we still expect that there will be more studies to establish the treadmill exercise model.